Kidney Failure Risk Equation and Cost of Care in Patients with Chronic Kidney Disease. Issue 1 (January 2022) - Prasad, Bhanu; Osman, Meric; Jafari, Maryam; Gordon, Lexis; Tangri, Navdeep; Ferguson, Thomas W.; Jin, Shan; Kappel, Joanne; Kozakewycz, Diane
Visual Abstract: Abstract : Background and objectives: Patients with CKD exhibit heterogeneity in their rates of progression to kidney failure. The kidney failure risk equation (KFRE) has been shown to accurately estimate progression to kidney failure in adults with CKD. Our objective was to determine health care utilization patterns of patients on the basis of their risk of progression. Design, setting, participants, & measurements: We conducted a retrospective cohort study of adults with CKD and eGFR of 15–59 ml/min per 1.73 m 2 enrolled in multidisciplinary CKD clinics in the province of Saskatchewan, Canada. Data were collected from January 1, 2004 to December 31, 2012 and followed for 5 years (December 31, 2017). We stratified patients by eGFR and risk of progression and compared the number and cost of hospital admissions, physician visits, and prescription drugs. Results: In total, 1003 adults were included in the study. Within the eGFR of 15–29 ml/min per 1.73 m 2 group, the costs of hospital admissions, physician visits, and drug dispensations over the 5-year study period comparing high-risk patients with low-risk patients were (Canadian dollars) $89, 265 versus $48, 374 ( P =0.008), $23, 423 versus $11, 231 ( P <0.001), and $21, 853 versus $16, 757 ( P =0.01), respectively. Within the eGFR of 30–59 ml/min per 1.73 m 2 group, the costs of hospital admissions, physician visits, and prescription drugs were $55, 944 versus $36, 740 ( P =0.10), $13, 414 versus $10, 370 ( P =0.08), and $20, 394 versus $14, 902 ( P =0.02) in high-risk patients in comparison with low-risk patients, respectively, for progression to kidney failure. Conclusions: In patients with CKD and eGFR of 15–59 ml/min per 1.73 m 2 followed in multidisciplinary clinics, the costs of hospital admissions, physician visits, and drugs were higher for patients at higher risk of progression to kidney failure by the KFRE compared with patients in the low-risk category. The high-risk group of patients with CKD and eGFR of 15–29 ml/min per 1.73 m 2 had stronger association with hospitalizations costs, physician visits, and drug utilizations.